(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Myth is sacred or symbolic story from the past, and it may be ritualistic in nature. A myth can be described as the origins of people, or explains customs or traditions. It is true that retelling of mythology is a common practice in literature. It is believed that the use of retelling of myths in literature with special reference of Indian English literature has undergone remarkable changes. The knowledge of Indian traditions and culture is seen through an alternative perspective. The quest for Indian traditions and culture in the writings of Amish Tripathi turns into a quest for identity and the true nature of Indian traditions, education and culture. Treatment of women empowerment in the writings of Amish Tripathi is also remarkable. In ancient time the role of education especially women education is remarkable. Most of the Women were educated in ancient times. They know the knowledge of Vedas and Puranas and skilled in medicine and administration. In the novels of Amish Tripathi education plays an important role. Most of his characters are well educated. The tradition and culture of India is described as the phenomenon of Indian society. The setting of the Shiva Trilogy is 1900 B.C. where each nation of the world become a representative of definite ideological system through its social governmental principal.